Bombardiers and assassins: mimetic interactions between unequally defended insects - Sugiura, Shinji; Hayashi, Masakazu (PeerJ, 2023)
In defensive mimicry, resemblance between unequally defended species can be parasitic; this phenomenon has been termed quasi-Batesian mimicry. Few studies have used real co-mimics and their predators to test whether the mimetic interactions were parasitic. Here, we investigated the mimetic interaction between two well-defended insect species, the bombardier beetle Pheropsophus occipitalis jessoensis (Coleoptera: Carabidae) and the assassin bug Sirthenea flavipes (Hemiptera: Reduviidae), using their potential predator, the pond frog Pelophylax nigromaculatus (Anura: Ranidae), which coexists with these insect species in the same habitat in Japan. We observed behavioural responses of this frog species (adults and juveniles) to adult Ph. occipitalis jessoensis and adult S. flavipes under laboratory conditions. Among the frogs, 100% and 75% rejected Ph. occipitalis jessoensis and S. flavipes, respectively, suggesting that, compared with the assassin bug S. flavipes, the bombardier beetle Ph. occipitalis jessoensis is more well-defended against frogs. An assassin bug or a bombardier beetle was provided to a frog that had encountered the other insect species. Frogs with a history of assassin bug encounter demonstrated a lower rate of attack toward bombardier beetles. Similarly, frogs with a history of bombardier beetle encounter demonstrated a lower rate of attack toward assassin bugs. Therefore, both the bombardier beetle Ph. occipitalis jessoensis and the assassin bug S. flavipes benefit from the mimetic interaction.
Keywords: Assassin bugs; Bombardier beetles; Brachinini; Carabidae; Chemical defences; Co-mimics; Frogs; Müllerian mimicry; Quasi-Batesian mimicry; Reduviidae